Development of Floating Tablets of Metformin HCl by Thermoplastic Granulation. Part II: In Vitro Evaluation of the Combined Effect of Acacia Gum/HPMC on Biopharmaceutical Performances - Mohamed Djebbar; Nacéra Chaffai; Fatiha Bouchal (Tabriz University of Medical Sciences, 2020)
Purpose: The aim of this study was to evaluate the combined effect, acacia gum(AG)/ hydroxypropylmethylcellulose (HPMC), on biopharmaceutical performances of floating tablets of metformin hydrochloride (MTH) prepared by thermoplastic granulation using stearic acid. Methods: We have prepared the matrixes using AG/HPMC as a polymer combination. This combination of polymers which represents 15% of the total mass of tablet was used at various ratios 3:1, 1:1, 1:3, with two viscosity grade of HPMC (k15M and k100M). The developed matrixes have been evaluated for their pharmacotechnical and biopharmaceutical properties. Results: In addition to the satisfactory physical characteristics of matrixes, it was revealed that the Fc3 and Fc6 formulations with AG/HPMC k15M and AG/HPMC k100M respectively, at ratio, 1:3 were considered the most performance. These formulations have shown swelling, fast flotation, 360 and 480 seconds respectively, and remained floating on the surface of the medium for more than 24 hours, with the matrix integrity, while F1, containing only AG, did not show swelling and did not float. In addition, extended in vitro release (>8 hours) with decreased dissolved MTH rates was demonstrated for Fc3 and Fc6 matrixes, 95% and 91% respectively, compared to F1 where MTH dissolution was complete after 2 hours. The drug release from the highest-performance matrixes (Fc3 and Fc6) was found to follow Korsmeyer-Peppas's model. The mechanism drug release was controlled by diffusion and erosion. Conclusion: The AG/HPMC combination was suitable as a polymer matrix to improve the in vitro biopharmaceutical properties of MTH compared to AG.